Apigenin Inhibits IL-6 Transcription and Suppresses Esophageal Carcinogenesis - Qiu, Jian-Ge; Wang, Lin; Liu, Wen-Jing; Wang, Ju-Feng; Zhao, Er-Jiang; Zhou, Feng-Mei; Ji, Xiang-Bo; Wang, Li-Hong; Xia, Zhong-Kun; Wang, Wei; Lin, Marie Chia-mi; Liu, Ling-Zhi; et al. (Frontiers in Pharmacology, 2019)
Esophagus cancer is the seventh causes of cancer-related deaths globally. In this study, we analyzed IL-6 gene expression in human esophagus cancer patients, and showed that IL-6 mRNA levels are significantly higher in tumor tissues and negatively correlated with overall survival, suggesting that IL-6 is a potential therapeutic target for esophagus cancer. We further demonstrated that apigenin, a nature flavone product of green plants, inhibited IL-6 transcription and gene expression in human esophagus cancer Eca-109 and Kyse-30 cells. Apigenin significantly and dose-dependently inhibited cell proliferation, and promoted apoptosis while stimulating the cleaved PARP (C-PARP) and Caspase-8 expression. It suppressed VEGF expression, and tumor-induced angiogenesis. Pretreatment of cells with IL-6 could completely reverse apigenin induced cellular changes. Finally, using a preclinical nude mice model subcutaneously xenografted with Eca-109 cells, we demonstrated the in vivo anti-tumor activity and mechanisms of apigenin. Taken together, this study revealed for the first time that apigenin is a new IL-6 transcription inhibitor, and that inhibiting IL-6 transcription is one of the mechanisms by which apigenin exhibits its anti-cancer effects. The potential clinical applications of apigenin in treating esophagus cancer warrant further investigations.